Do Private Schools Manage Better? - Alex Bryson; Francis Green (Institute of Labor Economics (IZA), 2018)
There is a perception among some commentators and policy analysts that leadership and managerial practices in private schools are superior to those in state schools. Analysing a survey of workplaces in Britain, we find little evidence to support this contention when examining the prevalence of modern human resource management (HRM) practices in schools. Rather, the evidence points to greater use of such practices in state schools. Those practices are correlated with improved school performance in the state sector, but not in the private sector. We discuss the implications of these findings for the policy of encouraging managers of private schools to sponsor state schools.
Keywords: I21; 330; school performance; human resource management